Stability Constants of Mixed Ligand Complexes of Transition Metal(II) Ions with N-(2-Hydroxy-1-naphthylidene)-2,6-diisopropylaniline as Primary Ligand and N-(2-Hydroxybenzylidene)-2,3-dimethylaniline as Secondary Ligand - A. K. Mapari; K. V. Mangaonkar (E-Journal of Chemistry)
Binary and ternary complexes of the type M-Y and M-X-Y [M = Co(II), Ni(II), Cu(II) and Zn(II); X = N-(2-hydroxy-1-naphthylidene)-2,6-diisopropylaniline and Y = N-(2-hydroxybenzylidene)-2,3-dimethylaniline] have been examined pH-metrically at 27±0.5 °C and µ = 0.1 M in 75: 25% (v/v) 1,4-dioxne-water medium. The logarithms of the values of stability constants for binary (M-Y) and for ternary (M-X-Y) systems were calculated.